Diagnostic value of RDW for the prediction of mortality in adult sepsis patients: A systematic review and meta-analysis - Wu, Hongsheng; Liao, Biling; Cao, Tiansheng; Ji, Tengfei; Huang, Jianbin; Ma, Keqiang (Frontiers in Immunology, 2022)
Methods We searched PubMed, Cochrane Library, Springer and Embase between Jan1, 2000 and May 30, 2022 for the primary studies about this research. We collected the articles that investigated red blood cell distribution width for varying degrees of sepsis patients-those who suffered from sepsis, severe sepsis or sepsis shock. Studies of healthy people and sepsis about children and neonate excluded from our research. The definition of study characteristics and data extraction were finished by two independent researchers, and discrepancies resolved by consensus. The combined sensitivities and specificities calculated through the meta-analysis. The sensitivity of the including studies were analyzed by excluding the studies which had potential heterogeneity. Summary operating characteristic curve was made to evaluate the diagnostic value for the prediction of mortality in adult sepsis patients. Fagan Test used to explore likelihood ratios and post-test probabilities. Finally, we investigated the source of heterogeneity using meta-regression. Results 24 studies including 40763 cases altogether brought into this analysis. Bivariate analysis indicated a combined sensitivity of 0.81(95%CI 0.73-0.86) and specificity of 0.65(95%CI 0.54-0.75).The area under the summary operating characteristic curve (SROC) was 0.81(95%CI 0.77-0.84). Substantial heterogeneity resided in the studies (I2=96.68, 95%CI 95.95-97.4). Meta-regression showed that the reference description, the prospective design and the blinded interpretation of the study results could be responsible for the heterogeneity.